Comparative phenomics and genomics of carbapenem-resistant escherichia coli from human and broiler chicken - Woldegiorgis, Erkihun Aklilu (2023)
The emergence of carbapenem-resistant Enterobacterales (CRE) has been alarming, and its control has been considered one of the priorities set by the World Health Organization (WHO). In Malaysia, recent reports show that the prevalence of CRE in general and tertiary hospitals has been alarmingly rising. However, little is known about the occurrence of CRE in animals, particularly food-producing animals such as broiler chickens in Malaysia. Moreover, there is no study on the comparative study of CRE from humans and food animals in Malaysia. Therefore, this study was conducted with the general objective of elucidating the comparative genomics of carbapenem-resistant Escherichia coli (CREC) from humans and broiler chickens. The study was conducted on clinical isolates archives of presumptive CREC isolates (n=32) from Hospital Universiti Sains Malaysia (HUSM), Kubang Kerian, and 384 cloacal swab samples of broiler chickens collected from East Coast Malaysia (Kelantan, Terengganu, and Pahang). Routine bacteriology followed by phenotypic and molecular characterization and determination of molecular epidemiology using multilocus sequence typing (MLST) were conducted. High-throughput Illumina HiSeqTM whole genome sequencing (WGS) of ten selected CREC isolates was done to determine the comparative genomics of the CREC isolates. The assembled genomes were annotated using RASTtk, BAKTA, and eggNOG-Mapper tools, and quantitative and qualitative measurements for ad-hoc downstream analyses were generated using M1CR0B1AL1Z3R server (Microbializer). Analyses of the WGS were done using ResFinder 4.1, VirulenceFinder 2.0, SerotypeFinder 2.0 tool, FimTyper version 1.0 CHTyper 1.0, cgMLST 1.2, pMLST (2.0), CSI Phylogeny, MobileElementFinder, Alien Hunter 1.7, ISFinder and IslandCompare (v1.0). Additional comprehensive genome analyses were done using different genomic analysis pipelines. The results showed an overall CREC detection rate of 7.29% (28/384) which is 10.94% (28) of the 256 E. coli isolated from cloacal swabs of broiler chickens based on phenotypic detection methods. Out of all the CREC, 40% (24/60) of the CREC isolates from human and broiler chickens harbor more than one carbapenemase gene, including the combinations blaNDM+blaOXA-48, blaNDM+blaOXA-48+blaIMP, and blaOXA-48+blaIMP. The molecular typing using MLST showed the detection of ST69, ST131, ST155, ST405, and ST410, which have been recognized as high-risk pandemic lineages. The comparative genomic analyses showed close similarities between CREC isolates from human and broiler chickens, which were evident from almost all the genomic profiles, including phylogeny, genomic islands, SNP analysis, plasmid, serotyping, and cgMLST and other genomic and proteome profiles. The comparative genomic analysis results showing similarities among CREC isolates from humans and apparently healthy chickens are important epidemiological data on CREC in human and broiler chickens in Malaysia. The findings from this study can help in better understanding the local CREC epidemiology and shed light on the possible CRE transmission dynamics in the local context. These findings, in turn, can help in devising of evidence-based control and prevention strategies that can contribute to the national antimicrobial resistance control programs to safe guard the public health.